Pengaruh Penerapan Sistem Informasi Akuntansi, Sistem Pengendalian Internal, dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan Kota Payakumbuh - Yovani, Yovani; Fitra, Halkadri (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to examine the impact of implementing accounting information systems, internal control systems, and human resource competencies on the quality of financial reports in Payakumbuh City. The research population consisted of 31 regional apparatus organizations (OPDs) in Payakumbuh City. Samples were selected using a purposive sampling technique with a total of 62 respondents representing the saturated sample. The data were analyzed using multiple linear regression analysis. The findings revealed that: 1) The application of accounting information systems significantly influences the quality of financial reports of regional apparatus organizations in Payakumbuh City. 2) The internal control system significantly affects the quality of financial reports of these organizations. 3) Competence of human resources significantly impacts the quality of their financial reports. For future studies, it is recommended to incorporate direct interview methods for data collection, include additional variables to verify the consistency of findings, and broaden the scope of the research objects to enhance generalizability.